Grand Variable Herz-Morrey Type Besove Spaces and Triebel-Lizorkin Spaces (European Journal of Pure and Applied Mathematics, 2025)
In the article, the boundedness of vector-valued sublinear operators in grand variable Herz-Morrey spaces $M \dot{K}_{ λ, p(·)}^{η (·), q), θ}\left(\mathbb{R}^{n}\right)$ are obtained. Then grand variable Herz-Morrey type Besov and Triebel-Lizorkin spaces are defined. We will also prove the equivalent quasi-norms by Peetre's maximal operators in these spaces.